Improving Literacy Skills of Students with Different Learning Styles Using E-6tslearning - Pradnya Permanasari; Ida Ayu Panuntun; Rizka Hayati (Jurnal Lingua Idea, 2021)
This research was aimed at describing what learning styles dominate the students' reading and writing abilities and how E-6tslearning improve the the fourth semester students’ reading and writing skills of the English Language Education Study Program of Teacher Training and Education Faculty of Pekalongan University. The writer used classroom action research (CAR) with 28 students as samples. The writer used planning, acting, observing and reflecting cycles. The writer used questionnaires to determine students’ learning styles and their satisfaction with the use of E-6tslearning and tests to measure their reading and writing skills. The results of the questionnaire analysis showed that there were three learning styles; those were visual, auditory and kinesthetic. From the results of the comparison of pre-test and post-test, students with kinesthetic learning styles experienced the best improvement of all, the visual group was the second one and the auditory group got the lowest achievement. The results of the pre-test and post-test comparison show an improvement in students' skills and motivation. This proves that the use of e-6tslearning can improve students' reading and writing skills. The results of the questionnaire analysis of student satisfaction on the use of e-6tslearning shows that learning by using e-6tslearning, students can improve their reading and writing skills and digital literacy. They can learn with fun with and without lecturer’s assistance.